Subjective Effects of Career Counselling and Client’s Satisfaction: An Analysis of Processes and Causes - Bernaud, Jean-Luc; Di Fabio, Annamaria; Saint-Denis, Caroline (Canadian Journal of Counselling and Psychotherapy, 2010)
This article studies the characteristics and determinants of subjective satisfaction and vocational effects after a career counselling session. A sample of 289 students from various specialties indicated, in addition to the subjective satisfaction and effects, that they evaluate counsellor and situation after the last step of career counselling. The results show that although only a third of the students said they were satisfied with the career counselling, a significant proportion (more than 90%) said they noted some effects, particularly in regard to self-knowledge and career knowledge. In addition, the nature of the academic guidance, the use of psychological tests, and the quality of service strongly contribute to an explanation of satisfaction and effects. The article discusses possible extensions of the research and offers recommendations for the improvement of career counselling.